Antibody against synthetic peptide of prolactin-inducible protein homologue precursor (PIP-HP) of Bali Cattle (Bos javanicus) saliva as a potential biomarker for immunoassay development - Kisworo, Djoko; Depamede, Sulaiman Ngongu (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: The present study aimed to produce and analyze antibody against a synthetic amino acid sequence fragment of PIP-HP of Bali cattle saliva. Materials and Methods: The synthetic amino acid sequence of the PIP-HP (VIRELGICPDDWAVIPIKANRF) was developed, conjugated to bovine serum albumin and was used to immunize Indonesian local rabbits. Positive sera that specific against the PIP-HP were pooled and purified sequentially by implying ammonium sulfate precipitation and protein A affinity methods. Purified antibody was then employed to analyze of PIP-HP in the ruminants’ saliva by means of westernblot assays. Results: A polyclonal antibody specific to asynthetic amino acid sequence fragment of PIP-HP of Bali cattle saliva was successfully produced. Our results show that the antibody potentially to be used to develop an immuno-diagnostic kit. Furthermore, the antibody was also able to inhibit the growth of both Escherichia coli and Staphylococcus aureus cultures significantly (P<0.001) at concentration of 0.3 mg/mL. Conclusions: In this study, antibody against synthetic peptide of PIP-HP (VIRELGICPDDWAVIPIKANRF) of Bali cattle saliva origin has been produced successfully. Further studies need to be carried out since the antibody has potential as biomarker for non-invasive immunoassays development. http://doi.org/10.5455/javar.2018.e264